Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $\{e_0, e_1, \dots, e_{N-1} \}$ be the Euclidean basis for $l^2(Z_N)$, and let $\{F_0, F_1, \dots, F_{N−1} \}$ be the Fourier basis( where $F_m(n)= \frac{1}{N} e^{2 \pi i m n/N}$ and $\hat{z}(m) = \sum_{n=0}^{N-1} z(n) e^{-2 \pi i m n/N}$).

  1. How to show that $\hat{e}_m(k) = e^{−2πimk/N}$ for all $k$? Notice that $\hat{e}_m$ is very nearly (up to a reflection and a normalization) an element of the Fourier basis.
  2. How to show that $\hat{F}_m = e_m$?
share|cite|improve this question

These follow immediately from the definition of the Fourier transform. You may be confusing yourself with "e"s.

share|cite|improve this answer
But how do they follow immediately from the definition of the Fourier transform? Could you explain a little bit, because I have got following, but I'm not satisfied with this solution of mine. $\hat{e}_m(k) = \sum_{n=0}^{N-1} e_m(k) e^{-2 \pi i m k/N} = e^{-2 \pi i m k/N}$ ii. How to show that $\hat{F}_m = e_m$? (my solution: $\hat{F}_m = \sum_{n=0}^{N-1} \frac{1}{N}e^{2 \pi i m n/N} e^{-2 \pi i m n/N} = \sum_{n=0}^{N-1} \frac{1}{N} = ? $ Any comments on my solutions. – alvoutila Jan 10 '11 at 10:12

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.